Selectivity and feeding behavior of Saanen goats subjected to three nutritional levels - Barros Gomes, Helen Fernanda; Souza, Samuel Figueiredo de; Oliveira, Daiana de; Biagioli, Bruno [UNESP]; Molina de Almeida Teixeira, Izabelle Auxiliadora [UNESP]; Resende, Kleber Tomas de [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
This study was conducted to investigate the effect of selective feeding habits on the quality of the ingested diet and the effect of feed restriction on the selectivity and behavior of goats in feedlots. Differences were found only in the amount of feed given to the animals, with a difference in the amount of feed rejected as a function of the nutritional level. Higher levels of orts were measured for those animals that received the ad libitum diet. For the composition of orts, differences were measured only in the ether extract fraction. Animals fed the ad libitum diet increased their intake of ether extract and energy, crude fiber, neutral detergent fiber, and acid detergent fiber. Thus, they had a preference for consuming the fibrous and energetic portions of the diet to the detriment of the mineral matter. The granulometry influenced the leftovers for the male and female treatments only in the diet that contained the 2.00- and 0.063-mm sized particles, with larger leftovers for the females. There were statistical differences as a function of feeding level for time spent in rumination, with stereotypical behavior, and in time spent standing up or lying down. As a function of sex, the differences were the same variables, including the time spent with agonistic behavior. Animals that received the ad libitum diet had a greater gain and final weight, whereas the animals that received the 60% restricted diet had the lowest performance, as did the females. Feed restriction changed the natural feeding behavior of goats, with smaller feed particles preferred. The feed restriction and sex also influenced the time spent on nonproductive activities, and the animals became more restless, with females having a higher social behavior than males.
Keywords: granulometry; intake; rumination; small ruminant